Pengaruh Pembelajaran IPS Materi Sejarah Terhadap Sikap Nasionalisme Berbasis Kearifan Lokal Pada Peserta Didik Di MTs Al Mansur Biangloe Kabupaten Bantaeng - Ismail Ismail; Rasyid Ridha; Jumadi Jumadi (Universitas Negeri Makassar, 2022)
The purpose of this study was to find out 1) Social studies learning history material at MTs Al-Mansur Biangloe Regency. Bantaeng 2) The attitude of nationalism based on local wisdom in students at MTs Al-Mansur Biangloe, Bantaeng Regency. 3) The effect of learning social studies history material on the attitude of nationalism based on local wisdom in students at MTs Al Mansur Biangloe, Bantaeng Regency. This research is a quantitative research with the type of correlational research. The population in this study were 60 students of class IX and a sample of 52 using random sampling technique. Data analysis used simple regression analysis and t-test. The results showed that 1) Social studies learning with historical material was carried out well where the learning outcomes of students had met the learning mastery standards. The learning process carried out by social studies teachers has met existing procedures such as lesson planning, implementation, and evaluation of learning 2) The attitude of nationalism based on local wisdom at MTs Al-Mansur Biangloe, Bantaeng Regency is in the high category. This shows that the attitude of nationalism is shown by an attitude of self-sacrifice, love for the homeland, pride as an Indonesian nation and unity and integrity. 3) There is a positive and significant influence between social studies learning and historical material on the attitude of nationalism based on local wisdom. That is, social studies learning with historical material can increase the attitude of nationalism based on local wisdom of students at MTs Al-Mansur Biangloe, Bantaeng Regency.